2009
DOI: 10.1158/0008-5472.can-09-1684
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Stat3-Dependent Transcription Regulatory Network Involved in Metastatic Progression

Abstract: High levels of activated Stat3 are often found in human breast cancers and can correlate with poor patient outcome. We employed an activated ErbB2 mouse model of breast cancer to investigate the in vivo role of Stat3 in mammary tumor progression and found that Stat3 does not alter mammary tumor initiation but dramatically affects metastatic progression. Four-fold fewer animals exhibited lung metastases in the absence of Stat3 and a 12-fold reduction in the number of lung lesions was observed in animals bearing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 48 publications
(65 reference statements)
7
87
1
Order By: Relevance
“…Thus the coupled expression of ErbB2 and Cre recombinase precludes the possibility of obtaining ErbB2-expressing Crenegative 'escapee' populations that could possibly contribute to the tumor. Indeed, we successfully showed that this approach results in complete ablation of targeted allele in NIC mice harboring either Stat3 or ShcA conditional alleles (Ursini- Siegel et al, 2008;Ranger et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Thus the coupled expression of ErbB2 and Cre recombinase precludes the possibility of obtaining ErbB2-expressing Crenegative 'escapee' populations that could possibly contribute to the tumor. Indeed, we successfully showed that this approach results in complete ablation of targeted allele in NIC mice harboring either Stat3 or ShcA conditional alleles (Ursini- Siegel et al, 2008;Ranger et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Recently published data suggests that the pro-inflammatory functions of STAT3 during mammary gland involution may also have a critical role in mammary tumor progression. In this work, mammary epithelial disruption of STAT3 in transgenic mice expressing the ErbB2 oncogene provide compelling evidence that a STAT3-dependent pro-inflammatory program is required for the metastatic phase of tumor progression (Ranger et al, 2009). Although mammary tumor onset was not affected by ablation of STAT3, the resulting tumors rarely metastasized to the lung (Ranger et al, 2009).…”
Section: A Stat3 Dependent Transcription Regulatory Network Is Involvmentioning
confidence: 89%
“…In this work, mammary epithelial disruption of STAT3 in transgenic mice expressing the ErbB2 oncogene provide compelling evidence that a STAT3-dependent pro-inflammatory program is required for the metastatic phase of tumor progression (Ranger et al, 2009). Although mammary tumor onset was not affected by ablation of STAT3, the resulting tumors rarely metastasized to the lung (Ranger et al, 2009). Remarkably, analyses of gene expression profile of these STAT3-deficient ErbB2 tumors revealed that the acute inflammatory response was dramatically impaired because of the reduced expression of C/EBPd, OSMR, SAA1 and SAA2.…”
Section: A Stat3 Dependent Transcription Regulatory Network Is Involvmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, disruption of Stat3 in mammary epithelium can have a profound impact on ErbB2-driven tumor progression. Although ErbB2 can induce tumors in the absence of Stat3, these tumors fail to metastasize (Ranger et al 2009). Examination of the gene expression profile of Stat3-deficient tumors revealed that they failed to induce the expression of a number of Stat3 target genes involved in inflammation (Ranger et al 2009).…”
Section: Erbb2 Signaling Impacts On Cell Cycle Progression and Transcmentioning
confidence: 99%